Freeze-dried fecal samples are biologically active after long-lasting storage and suited to fecal microbiota transplantation in a preclinical murine model of Clostridioides difficile infection - Julie Reygner; Christine Charrueau; Johanne Delannoy; Camille Mayeur; Véronique Robert; Céline Cuinat; Thierry Meylheuc; Aurélie Mauras; Jérémy Augustin; Ioannis Nicolis; Morgane Modoux; Francisca Joly; et al. (Gut Microbes, 2020)
Fecal microbiota transplantation is now recommended for treating recurrent forms of Clostridioides difficile infection. Recent studies have reported protocols using capsules of either frozen or freeze-dried stool allowing oral administration in in- and out-patient settings. However, a central question remains the viability, engraftment, and efficacy of the microbiome over time during storage life. This study shows that both the freeze-drying and freezing procedures for fecal samples allowed preserving viability, short-chain fatty acids concentration, and anti-Clostridioides difficile properties of microbiota without significant alteration after storage for 12 months. Fecal transplantation with freeze-dried microbiota allowed engraftment of microbiota leading to clearance of Clostridioides difficile infection in a preclinical murine model with a survival rate of 70% versus 53-60% in mice treated with frozen inocula, and 20% in the untreated group. Moreover, the freeze-dried powder can be used to fill oral hard capsules using a very low amount (0.5%) of glidant excipient, allowing oral formulation. Altogether, this study showed that freeze-dried inocula can be used for the treatment of Clostridioides difficile infection with long-lasting stability of the fecal microbiota. This formulation facilitates biobanking and allows the use of hard capsules, an essential step to simplify patient access to treatment.